Testing Enhances Subsequent Learning in Older Adults - Pastötter, Bernhard; Bäuml, Karl-Heinz T. (Psychology and aging)
Interference susceptibility has been suggested to be a major factor for episodic memory impairment in healthy older adults. Previous work has shown that retrieval practice can reduce proactive interference and thus enhance learning and memory in younger adults, a finding referred to as the forward effect of testing in the literature. This study examined the late developmental trajectory of the forward effect in middle-aged and older adults (40 to 79 years of age). Participants studied three lists of items in anticipation of a final cumulative recall test. In the testing condition, participants were tested immediately on Lists 1 and 2 after initial study, whereas in the restudy condition, they restudied Lists 1 and 2. In both conditions, participants were tested immediately on List 3. The results of the immediate List-3 recall test showed a reliable forward effect of testing, with interim testing of Lists 1 and 2 enhancing List-3 recall and reducing the number of prior-list intrusions. Notably, this effect of testing was found independent of participants' age. These results suggest that retrieval practice can reduce proactive interference in middle-aged and older adults. Together with recent findings on the presence of the backward effect of testing in older adults-that is, improved recall of studied material after retrieval versus restudy, these findings indicate that retrieval practice can be a very powerful tool to delimit memory impairment in older age.